Transcriptomic insights into the dominance of two phototrophs throughout the water column of a tropical hypersaline-alkaline crater lake (Dziani Dzaha, Mayotte) - Duperron, Sébastien; Halary, Sébastien; Bouly, Jean-Pierre; Roussel, Théotime; Hugoni, Myléne; Bruto, Maxime; Oger, Philippe M.; Duval, Charlotte; Woo, Anthony; Jézéquel, Didier; Ader, Magali; Leboulanger, Christophe; et al. (Frontiers in Microbiology, 2024)
Saline-alkaline lakes often shelter high biomasses despite challenging conditions, owing to the occurrence of highly adapted phototrophs. Dziani Dzaha (Mayotte) is one such lake characterized by the stable co-dominance of the cyanobacterium Limnospira platensis and the picoeukaryote Picocystis salinarum throughout its water column. Despite light penetrating only into the uppermost meter, the prevailing co-dominance of these species persists even in light-and oxygen-deprived zones. Here, a depth profile of phototrophs metatranscriptomes, annotated using genomic data from isolated strains, is employed to identify expression patterns of genes related to carbon processing pathways including photosynthesis, transporters and fermentation. The findings indicate a prominence of gene expression associated with photosynthesis, with a peak of expression around 1m below the surface, although the light intensity is very low and only red and dark red wavelengths can reach it, given the very high turbidity linked to the high biomass of L. platensis. Experiments on strains confirmed that both species do grow under these wavelengths, at rates comparable to those obtained under white light. A decrease in the expression of photosynthesis-related genes was observed in L. platensis with increasing depth, whereas P. salinarum maintained a very high pool of psbA transcripts down to the deepest point as a possible adaptation against photodamage, in the absence and/or very low levels of expression of genes involved in protection. In the aphotic/anoxic zone, expression of genes involved in fermentation pathways suggests active metabolism of reserve or available dissolved carbon compounds. Overall, L. platensis seems to be adapted to the uppermost water layer, where it is probably maintained thanks to gas vesicles, as evidenced by high expression of the gvpA gene. In contrast, P. salinarum occurs at similar densities throughout the water column, with a peak in abundance and gene expression levels which suggests a better adaptation to lower light intensities. These slight differences may contribute to limited inter-specific competition, favoring stable co-dominance of these two phototrophs.